"Gathered around the Sign of the Littorio": The Italo-Abyssinia Conflict and Its Impact on Italian Fascism in Queensland, 1935–1939 - Brown, David (Spunti e Ricerche, 2016)
This article examines the progression of fascist support amongst the Italian communities of Queensland in the 1930s with a specific focus on the celebrations concerning Italy's victory in the Abyssinian War. This event saw the largest celebrations in support of the Italian fascist government by Queensland Italians and enabled the state's fascist organisations to mobilise the support of the Italian population in a way they had previously been unable to achieve. What does this demonstrate about the nature of fascist support in Queensland and the forces that shaped the interaction between Italians and the Partito Nazionale Fascista in this state? This article uses the specific focus on the reaction to the Abyssinian War amongst the state's Italians to illuminate those particular factors that could encourage widespread support for fascism and, thus, a more complex understanding of the Italian population's relationship with the Queensland fascist associations.